Estimativa de propriedades mecânicas de madeiras de Eucalipto em função de parâmetros físicos e anatômicos - Marini, Lucas José (Universidade Federal de São Carlos, 2022)
Exotic species introduced in Brazil have been of great interest to the civil construction industry because, among their advantages, they have rapid growth and provide sustainability for intensively exploited native species. In reforestation activities, the use of the Eucalyptus genus is verified as it has several species used to generate products and by-products. It is important to emphasize that the knowledge of the mechanical properties of wood allows its rational application with greater safety and functionality in structural projects, however, the tests to determine these properties demand technical training and specific equipment, found only in developed research centers. An alternative to understand the properties of wood is the use of optical microscopy, consequently, in this study an Olympus EX51 microscope was used to determine the anatomical elements of wood, aiming to demonstrate the feasibility of estimating the mechanical properties of Eucalyptus wood as a function of its anatomical parameters and bulk density, through regression models. To carry out the analysis, 10 lots of Eucalyptus of different species were used, and the tests developed consisted of determining the bulk density, strength to compression parallel to the grain, strength to tensile parallel to the grain, strength to tensile normal to the grain, the modulus of elasticity in compression parallel to the grain, the modulus of elasticity in tensile parallel to the grain, shear strength parallel to the grain, shrinkage, as well as of anatomical parameters (fibers, vessels and radii) of the samples, according to the Brazilian standards ABNT NBR 7190 (1997) and ABNT NBR 15066 (2004). The proposed regression models were excellent, as the R² values were equal to 94.15, 92.95, 90.55, 86.55, 77.77 and 67.95% for estimating the modulus of elasticity in compression parallel to the grain, strength to compression parallel to the grain, modulus of elasticity in tensile parallel to the grain, strength to tensile parallel to the grain, shear strength parallel to the grain and strength to tensile normal to the grain, respectively.
Estimation of mechanical properties in Eucalyptus woods towards physical and anatomical parameters
Keywords: Eucalyptus; Propriedades mecânicas; Modelos de regressão; Anatomia da madeira; Densidade aparente; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL; ENGENHARIAS::ENGENHARIA CIVIL::ESTRUTURAS